Meningkatkan Kemampuan Tata Bahasa Siswa Melalui Penggunaan Wayground Quiz pada Kelas XI Sekolah Menengah Atas - Noftriana, Eka; Musyarofah, Lailatul (Jurnal Pendidikan : Riset dan Konseptual, 2026)
This classroom action research investigates the effectiveness of Wayground Quiz in improving the grammar mastery of eleventh-grade students at a senior high school. The study was conducted in two cycles, each consisting of planning, acting, observing, and reflecting stages. The participants were eleventh-grade students whose main difficulties included the use of tenses, subject–verb agreement, and pronouns. Data were collected through grammar tests, classroom observations, and students’ questionnaires. The results indicate that the implementation of Wayground Quiz significantly enhanced students’ grammar achievement as well as their motivation and participation in learning. Quantitatively, students’ mean grammar scores improved from 65.50 in the first cycle to 82.15 in the second cycle, showing a 25.42% increase and surpassing the minimum mastery criterion. Qualitative findings from observations and questionnaires reveal that students became more active, confident, and enthusiastic during grammar activities. They responded positively to the digital quiz features such as immediate feedback, time limits, and competitive elements, which made grammar practice more engaging and less monotonous. The study concludes that integrating Wayground Quiz into grammar instruction can effectively improve students’ grammar performance and create a more enjoyable and interactive learning environment for senior high school students